Inovasi Kebudayaan: Tari Chit Ngiat Pan: Refleksi Hubungan Sosial atas Semboyan “Tong Ngin Fan Ngin Jit Jong” - Yessi Nirmala; Aimie Sulaiman; Jamilah Cholillah (Inovbook, 2021)
This study analyzes innovation, one of which is cultural innovation. The culture studied is a culture that is formed as the result of cultivation or human creativity which is called art, especially dance art. The focus of this research is to discuss the reflection of social relations on the motto